Association of use of statins with progression of diabetic retinopathy: a randomized controlled trial at a tertiary care centre in Southern India - Khan, Shehla Ashraf; Andanappa, Adithya; Kukunoor, Hanisha Reddy; Naidu, Sirapurapu Veera Venkata Laxmaiah; Toodi, Abhijeeth Reddy (International Journal of Research in Medical Sciences, 2025)
Background: Diabetic retinopathy (DR) is a major microvascular complication of type 2 diabetes mellitus (T2DM) and a leading cause of vision impairment globally. Statins, beyond their lipid-lowering and cardiovascular benefits, may offer protective effects against DR by reducing inflammation, stabilizing endothelial function and modulating vascular endothelial growth factor (VEGF) expression. This study aimed to assess the impact of statin therapy on DR severity in patients with T2DM. Methods: A randomized controlled trial was conducted at Government General Hospital, Srikakulam, between April 2024 and February 2025. A total of 120 patients with DR were enrolled and divided into two groups: those receiving statin therapy and those not on statins. DR severity was assessed using fundus examination findings and compared between the two groups. Results: Among the 60 patients on statins, 62.2% had mild non-proliferative diabetic retinopathy (NPDR), while only 3.3% had proliferative DR (PDR) and 1.7% had diabetic macular edema (DME). In contrast, among non-statin users, only 18.2% had mild NPDR, while 29.1% had severe NPDR, 14.5% had PDR and 7.3% had DME. One patient also had vitreous hemorrhage. Conclusions: Statin therapy appears to be associated with milder forms of DR in patients with T2DM. These findings suggest that statins may help slow DR progression, highlighting their potential as an adjunctive therapy for retinal protection in diabetes management.